Business lessons from the edge [electronic resource] : learn how extreme athletes use intelligent risk-taking to succeed in business - McCormick, Jim; Karinch, Maryann (McGraw-Hill, 2009)
Reveals the winning mindset of top extreme sports athletes who have translated their experiences into business success by relying on the same principles of risk-taking, preparation, and self-confidence.